2014
DOI: 10.2807/1560-7917.es2014.19.31.20869
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcome of invasive pneumococcal disease among adults in Belgium, 2009–2011

Abstract: NoteVariation assessment report as adopted by the CHMP with all information of a commercially confidential nature deleted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 20 publications
(33 reference statements)
2
29
1
2
Order By: Relevance
“…To These serotypes were selected because they are immunogenic (20) and have been prevalent in Belgium over the last 15 years (21,22). SCID mice reconstituted with CD19 ϩ CD5 Ϫ B cells produced significantly higher levels of IgG antibodies than did SCID mice reconstituted with CD19 ϩ CD5 ϩ B cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To These serotypes were selected because they are immunogenic (20) and have been prevalent in Belgium over the last 15 years (21,22). SCID mice reconstituted with CD19 ϩ CD5 Ϫ B cells produced significantly higher levels of IgG antibodies than did SCID mice reconstituted with CD19 ϩ CD5 ϩ B cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PCV serotypes were responsible for >60% of total serotypes in IPD cases in few studies among adults aged 65 y and older 6,58 and 15-59 y. 6,57 Overall, serotypes 1, 4, 14 and 19A were among the most prevalent PCV serotypes among adults with IPD, while serotype 3 is the most common PCV serotype among adult IPD cases in North America. While the current picture suggests that the availability of PCVs may have had a great effect in targeting PCV-specific serotypes among adult IPD cases, the introduction of PCV7 previously led to an overall reduction in the incidence of all-type IPD ranging from 80% in the US to 30-40% in Europe among children aged less than 5 y.…”
Section: Discussionmentioning
confidence: 99%
“…30 Conjugate vaccine serotypes causing IPD were highly prevalent (> 60% of serotypes) in 2 studies. 6,57 Prevalence of serotypes uniquely covered by PPV23 was reported in 4 studies 6,9,24,57 2 of which reported 12F to be most prevalent. Other prevalent serotypes of note were 8 (4 studies; 4.7%), 6,9,24,57 22F (4 studies; 4.1%) 6,9,24,57 and 9N (3 studies; 3.5%).…”
Section: Pneumococcal Serotype Distribution Among Adults Aged 15-59 Ymentioning
confidence: 99%
See 2 more Smart Citations